Complicated War Trauma and Care of the Wounded : The Israeli Experience in Medical Care and Humanitarian Support of Syrian Refugees - Zarka, Salman; Lerner, Alexander (Springer International Publishing : Imprint: Springer, 2017)
This book presents carefully selected case reports that document some of the most important lessons learned at Ziv Medical Center, the northernmost Israeli hospital responsible for the medical care and support of wounded and patients from the Syrian civil war. The aim is to provide practitioners with new knowledge on effective ways of dealing with the emergencies encountered in the context of such conflicts. The case reports cover in particular the specialties of Trauma and Critical Care, Orthopedics, and Surgery, but also relate to Internal Medicine, Ophthalmology, Obstetrics and Gynecology, and Psychiatric Care. Some of the cases of trauma are of a nature not previously encountered by Western medicine, and include instances in which multidisciplinary care played a vital role. Featuring many informative illustrations, the book will be of value for all who work in emergency and military medicine and related disciplines, from novices to the more experienced.
Keywords: Medicine.; Emergency medicine.; Orthopedics.; Traumatology.; elektronické knihy; electronic books